Cognitive and clinical outcomes of homocysteine-lowering B-vitamin treatment in mild cognitive impairment: A randomized controlled trial - De Jager, C; Oulhaj, A; Jacoby, R; al., E (Wiley, 2012)
Background Homocysteine is a risk factor for Alzheimer's disease. In the first report on the VITACOG trial, we showed that homocysteine-lowering treatment with B vitamins slows the rate of brain atrophy in mild cognitive impairment (MCI). Here we report the effect of B vitamins on cognitive and clinical decline (secondary outcomes) in the same study. Methods This was a double-blind, single-centre study, which included participants with MCI, aged ≥70y, randomly assigned to receive a daily dose of 0.8mg folic acid, 0.5mg vitamin B 12 and 20mg vitamin B 6 (133 participants) or placebo (133 participants) for 2y. Changes in cognitive or clinical function were analysed by generalized linear models or mixed-effects models. Results The mean plasma total homocysteine was 30% lower in those treated with B vitamins relative to placebo. B vitamins stabilized executive function (CLOX) relative to placebo (P=0.015). There was significant benefit of B-vitamin treatment among participants with baseline homocysteine above the median (11.3μmol/L) in global cognition (Mini Mental State Examination, P<0.001), episodic memory (Hopkins Verbal Learning Test-delayed recall, P=0.001) and semantic memory (category fluency, P=0.037). Clinical benefit occurred in the B-vitamin group for those in the upper quartile of homocysteine at baseline in global clinical dementia rating score (P=0.02) and IQCODE score (P=0.01). Conclusion In this small intervention trial, B vitamins appear to slow cognitive and clinical decline in people with MCI, in particular in those with elevated homocysteine. Further trials are needed to see if this treatment will slow or prevent conversion from MCI to dementia.